JURISDICTION IN OUTER SPACE FROM THE PERSPECTIVE OF INTERNATIONAL LAW (American Journal of Research in Humanities and Social Sciences, 2025)
This research aims to clarify the principles governing the exploration and utilization of outer space, emphasizing the role of international law, particularly international criminal law, in addressing crimes committed beyond Earth whether aboard spacecraft, the International Space Station, or in outer space generally. It examines relevant international treaties governing outer space activities, evaluates their strengths and ambiguities, and highlights deficiencies in their provisions. Furthermore, the study analyzes traditional principles of state criminal jurisdiction territoriality, nationality, universality, and protection and assesses their applicability to offenses committed in outer space.